2019
DOI: 10.1515/nanoph-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced THz EIT resonance based on the coupled electric field dropping effect within the undulated meta-surface

Abstract: In this paper, the enhanced terahertz (THz) electromagnetically induced transparency (EIT) resonance is achieved based on the coupled electric field dropping effect within the undulated meta-surface. It is found that the height difference between the inner ring and the outer split ring could lead to a significant coupled mode with electric field dropping distribution. When the height of the inner ring increases, the electric field of the inner ring gradually cascades to the outer ring just as a waterfall so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…By adjusting the asymmetry parameter, the EIT-like effect in the perovskite MM structure could be controlled. Unlike previous studies [2,[47][48][49][50][51] on the EIT-like effect, it was found that there is a maximum value for the coupling strength between bright-dark modes. This implies that there is a region where the coupling strength increases or decreases with changes to the asymmetry parameter.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…By adjusting the asymmetry parameter, the EIT-like effect in the perovskite MM structure could be controlled. Unlike previous studies [2,[47][48][49][50][51] on the EIT-like effect, it was found that there is a maximum value for the coupling strength between bright-dark modes. This implies that there is a region where the coupling strength increases or decreases with changes to the asymmetry parameter.…”
Section: Discussioncontrasting
confidence: 93%
“…In the near-field coupling between bright and dark modes, the incident wave excites the bright mode, which transfers electromagnetic energy to the dark mode. This interaction can be described by the linearly coupled Lorentz harmonic oscillator model [49][50][51][52]:…”
Section: Eit-like Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, in order to create a single-band EIT-MM, the requirement is an MM structure consisting of, at least, two different types of resonators [26,27]. So far, to our knowledge, most of the multi-band EIT-MMs have exploited more than three different types of resonators in the structure [28][29][30].…”
Section: Introductionmentioning
confidence: 99%